Prevalence, Diagnosis, Perioperative Monitoring and Treatment of Right Ventricular Dysfunction and/or Pulmonary Arterial Hypertension in Cardiac Surgical Patients in Germany—A Postal Survey - Heringlake, Matthias; Schön, Julika; Pliet, Teresa; Haake, Nils; Reinecke, Alexander; Habicher, Marit; Sander, Michael; Markewitz, Andreas; Reuter, Daniel A.; Groesdonk, Heinrich Volker; Trummer, Georg; Pilarzyk, Kevin; von der Brelie, Michael; Bein, Berthold; Schirmer, Uwe (The Thoracic and Cardiovascular Surgeon, 2017)
Background Sparse data are available on the prevalence of right ventricular dysfunction and/or pulmonary arterial hypertension in patients scheduled for cardiac surgery in Germany as well as on the intensity and modalities used for diagnosis, perioperative monitoring, and treatment of these comorbidities.Methods A postal survey including questions on the prevalence of preoperative right ventricular dysfunction and/or pulmonary arterial hypertension in patients undergoing cardiac surgery in 2009 was sent to 81 German heart centers. Total 47 of 81 (58%) heart centers returned the questionnaires. The centers reported data on 51,095 patients, and 49.8% of the procedures were isolated coronary artery bypass grafting.Results Data on the prevalence of preoperative pulmonary hypertension and/or right ventricular dysfunction were not available in 54% and 64.6% of centers. In the remaining hospitals, 19.5% of patients presented right heart dysfunction and 10% pulmonary arterial hypertension. Preoperative echocardiography was performed in only 45.3% of the coronary artery bypass grafting cases. Preoperative pharmacologic treatment of pulmonary hypertension or right ventricular dysfunction with oral sildenafil, inhaled prostanoids, or nitric oxide was initiated in 71% and 95.7% of the centers, respectively. Intra- and postoperative treatment was most frequently accomplished with phosphodiesterase-III inhibitors.Conclusion The prevalence of preoperative right heart dysfunction and pulmonary arterial hypertension in cardiac surgical patients in Germany seems to be substantial. However, in more than 50% of the patients, no preoperative data on right ventricular function and pulmonary arterial pressure are available. This may lead to underestimation of perioperative risk and inappropriate management of this high-risk population.
Keywords: cardiac; pulmonary vascular resistance/hypertension; surgery; complications